STILISTIKA PENGULANGAN SEBAGAI TRANSFER IDEOLOGI (Telaah atas Pidato Politik Sayyed Hasan Nasrullah) - Habib Habib (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract:This paper will explore how the repetition serves as a transfer of medium of an ideology. Repetition (tikrar) in Arabic has been much explored by using several approaches. However, research on the relationship of repetition and ideology is still very rarely discussed. To deal with the Lebanese audience from different groups, Nasrullah focused on the use of stylistic repetition to reinforce the different political strategies. In addition, this paper will also demonstrate the ability of Nasrullah in choosing the different registers in accordance with its target audience. Nasrullah used lexical repetition in a speech to promote attitudes and political ideology. Keywords: -Arabic discourse; -ideology;- repetition; -political speech.